Evaluation of Methods of Volume-Production of Vodcasts of Presentations - McKee, William; Harrison, David K; Allan, Malcolm (International Journal of Emerging Technologies in Learning (iJET), 2008)
This paper describes traditional methods of production of videos of lecture presentations and argues that these are suitable only for a limited number of presentations due to the high cost of capture and post-production. The concept of making every presentation of every class available as a podcast is discussed, and methods of utilising low-cost technologies and applications to allow this to be achieved are compared. Experiences of pilot schemes utilising a variety of devices and commercial, freeware and self-written production methods will be presented, with comment on the usability of each approach at both capture and production stages.